Lace bite: A review of tibialis anterior tendinopathy in ice hockey players - Levitsky, M. M.; Turner Vosseller, J.; Popkin, C. A. (Translational Sports Medicine, 2020)
Ice hockey is a fast-paced collision sport with a high injury rate. Lower extremity pathology accounts for nearly one third of these injuries. Given the unique nature of the sport, there are various injuries seen more commonly in ice hockey players, including "late bite" (or "skate bite"). Lace bite is an inflammation of the tibialis anterior tendon which often affects hockey players in the beginning of the season. This is often caused by irritation of the tibialis anterior from the tongues of skates which have not yet been broken in. These patients often present with edema, tenderness over the anterior tibial tendon, and pain with dorsiflexion. Treatment of lace bite involves skate modifications such as breaking in the skate before increased play, and padding over the anterior ankle to reduce pressure from the tongue. Topical and systemic anti-inflammatories, along with icing and activity modification are also helpful in reducing symptoms. These injuries are often short-lived and resolve within 2 weeks. By having a better understanding of this injury, team physicians will be able to more promptly diagnose and effectively treat this condition.